Design and Simulation of Low Power and Voltage Micro Photovoltaic Cell for Mobile Devices - Ikbal Rullah; Robby Kurniawan Harahap; Eri Prasetyo Wibowo; Antonius Irianto Sukowati; Dyah Nur'ainingsih; Widyastuti Widyastuti (Universitas Muhammadiyah Malang, 2022)
In this study, designed and simulated a micro photovoltaic cell circuit which is part of smartphone battery charging system sensor. Problem discussed in this paper was that smartphone are still charging battery from PLN through a wall outlet, but smartphone would be better off if it had other charging alternatives, such as being able to charge anywhere or mobile. This paper proposed used photovoltaic cell that can convert sunlight into electricity and it can charge the battery on a smartphone. Photovoltaic cell were integrated with smartphone batteries in photovoltaic IC to form a battery charging system that can charge smartphone. The design of the micro photovoltaic cell sensor section is based on from the references paper. Micro photovoltaic cell was design by modifying the resistor value in the micro photovoltaic cell circuit, so the output low voltage and power be able to charge the smartphone battery. Designed and simulated micro photovoltaic cell circuits will be carried out using LTSpice. The results that achived in this research, when shunt resistance value was configure negative, the voltage value around 200mV, the power value around 1,48µW. When the shunt resistance value was configure positive the voltage value around 199mV, the power value around 1,44µW. Analysis was carried out by comparing voltage values obtained in this study with previous studies. In this study, a smaller voltage value was obtained by modifying the resistor value in the micro photovoltaic cell circuit. The circuit design will later be implemented in 0.35µm CMOS technology.